Analisis Pengaruh Pengembangan Kawasan Transit Oriented Development terhadap Nilai Tanah - Benito, Obed Juan; Riandoko, Riko (Polytechnic of State Finance STAN, 2023)
Accessibility is one of the important characteristics that can affect land value. The better the accessibility of a land site, the higher its value. One of the factors that support the level of accessibility of a land site is the distance between the land and public transportation facilities. This study analyzed the impact of a certain public transportation facility in Jakarta on the value of the surrounding land. A case study was conducted in the Fatmawati Transit Oriented Development area at South Jakarta. The Fatmawati MRT station is the center of that area. The data in this study were obtained by using literature study and field observation. Data analysis was carried out by establishing a model using the Geographically Weighted Regression (GWR) and Ordinary Least Squares (OLS) for data prediction. The prediction results of each model were processed using the interpolation method and the Kriging technique to obtain a geographical visualization of the distribution of land values in the study area. This study concludes that the Fatmawati Transit Oriented Development area has a significant effect on the value of the surrounding land.